2013
DOI: 10.5114/pdia.2013.37029
|View full text |Cite
|
Sign up to set email alerts
|

Current standards for diagnosis and treatment of syphilis: selection of some practical issues, based on the European (IUSTI) and U.S. (CDC) guidelines

Abstract: Syphilis continues to be an important epidemiologic problem. For a few years a steady increase in the incidence of this sexually transmitted disease has been observed. Advances in medical science obligate the doctor to use only such diagnostic and therapeutic approaches that are scientifically proven. Based on the European (IUSTI) and U.S. (CDC) guidelines, in this manuscript, we present some selected practical issues concerning diagnosis and treatment of syphilis. We truly hope that the present review will he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 19 publications
0
36
0
7
Order By: Relevance
“…Differences between our outcomes and those in previous studies may be due to an improved immune-status of HIV-positive patients because of highly active antiretroviral therapy (HAART). 26,27 In line with this, current IUSTI guidelines 1,12,13 state that HIV coinfected syphilitic patients should be treated as immunocompetent patients, except for those who have CD4þ cell counts of 350/lL.…”
Section: Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between our outcomes and those in previous studies may be due to an improved immune-status of HIV-positive patients because of highly active antiretroviral therapy (HAART). 26,27 In line with this, current IUSTI guidelines 1,12,13 state that HIV coinfected syphilitic patients should be treated as immunocompetent patients, except for those who have CD4þ cell counts of 350/lL.…”
Section: Hivmentioning
confidence: 99%
“…1,12,13 In special situations (pregnancy, allergy, or refusal of intravenous treatment), oral or intramuscular treatment can be considered. Improvement in VA at 1 and 6 months was seen in all groups of patients independent of the route of administration of antibiotics.…”
Section: Antibiotic Treatmentmentioning
confidence: 99%
“…115 Doxycycline, tetracycline, or erythromycin may be used for 116 patients who are allergic to penicillin. 4 127 Various types of cytokine secretion change during the different 128 stages of syphilis, and there has been a lot of research into cytokine 129 secretion in syphilis. In one study, it was found that the cells of 130 syphilitic patients were already able to produce interleukin (IL)-2, 131 interferon, tumor necrosis factor, and IL-10, and weakly IL-6, in 132 primary seronegative syphilis.…”
mentioning
confidence: 99%
“…20 Overall, the nontreponemal tests have a sensitivity of 86% in primary syphilis and 100% in secondary syphilis. At least 1 treponemal antigen test and 1 nontreponemal antigen test area sufficient to confirm syphilis.…”
Section: Diagnosis Of Syphilismentioning
confidence: 99%